Reliability, Knowledge Translation, and Implementability of the Spanish Version of the Hammersmith Infant Neurological Examination - Hidalgo-Robles, Álvaro (Healthcare, 2024)
Purpose. This study aimed to: (a) translate and cross-culturally adapt the Hammersmith Infant Neurological Examination (HINE) into Spanish; (b) evaluate its intra- and inter-examiner reliability; (c) support a knowledge translation and tool implementation program in early intervention; and (d) evaluate its reliability and implementation for professionals one year after receiving training. Materials and methods. The translation followed the World Health Organization’s recommendations. Reliability was assessed in 25 infants aged between 3 and 15 months with identifiable risks of cerebral palsy (CP). The implementation was also evaluated by analyzing the reliability of professionals without previous experience of the tool by using a pre-survey and a follow-up survey one year after training. The survey covered aspects related to the use of early detection tools of CP and the use of HINE, including attitudes, opinions, and perceptions. Results. An excellent intra- and inter-examiner agreement was obtained for the total score of the HINE intra-class correlation coefficient (ICC = 0.98 in both indices). One year after training, the professionals also showed excellent reliability values (ICC = 0.99), as well as an increase in sensitization and skills in evidence-based practices for the early detection of “high risk” of CP. Conclusions. The Spanish version of HINE is a reliable measure for the neurological evaluation of “high risk” of CP and can be administered after standardized training and without costs to acquire the evaluation. This allows its accessible and widespread implementation in the clinical context.
Keywords: Hammersmith infant neurological examination; early detection; cerebral palsy; reliability; knowledge translation